PENGARUH KEADILAN ORGANISASIONAL TERHADAP KECURANGAN DENGAN VARIABEL MODERATING KUALITAS PENGENDALIAN INTERNAL - Irmaya Sitarahmi; Mirna Dyah Praptitorini S (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
The purpose of this study was to examine the relationship betweenorganizational justice against fraud employees and test the quality ofinternal control as factors that strengthen or weaken the relationship betweenorganizational justice with employee fraud.This study uses primary data.Data taken directly from the respondents by using questionnaire technique to47 respondents in minimarket outlets that are the object of research in the cityof Semarang. Data were analyzed by simple regression analysis and residualtest.The results showed that suggests that organizational justice did notsignificantly affect employee fraud and the variable quality of internalcontrol is a moderating variable.